Contrast Sensitivity and Night Driving in Older People: Quantifying the Relationship Between Visual Acuity, Contrast Sensitivity, and Hazard Detection Distance in a Night-Time Driving Simulator - Jones, Pete R.; Ungewiss, Judith; Eichinger, Peter; Wörner, Michael; Crabb, David P.; Schiefer, Ulrich (Frontiers in Human Neuroscience, 2022)
Purpose: (i) To assess how well contrast sensitivity (CS) predicts night driving ability in normally sighted older drivers, relative to a conventional measure of high contrast visual acuity (VA); (ii) To evaluate whether CS can be accurately quantified within a night driving simulator. Methods: Participants were fifteen (five female) ophthalmologically healthy adults, aged 55 to 81 years. CS was measured in a driving simulator using Landolt Cs, presented under static or dynamic driving conditions, and with or without glare. In the dynamic driving condition, the participant was asked to simultaneously maintain a (virtual) speed of 60 km/h on a country road. In the (dynamic) with glare condition, two calibrated LED arrays, moved by cable robots, simulated the trajectories and luminance characteristics of the (low beam) headlights of an approaching car. For comparison, CS was also measured clinically (with & without glare) using an Optovist I instrument modified for an enhanced contrast range towards low contrast levels (Vistec Inc., Olching/FRG). Visual acuity (VA) thresholds were also assessed at high and low contrast using the Freiburg Visual Acuity Test (FrACT) under photopic conditions. As a measure of driving performance, median hazard detection distance (MHDD) was computed, in meters, across three kinds of simulated obstacles of varying contrast. Results: CS and low contrast VA were both significantly associated with driving performance (both P < 0.01), whereas conventional high contrast acuity was not (P = 0.10). There was good agreement (P < 0.01) between CS measured in the driving simulator and a conventional clinical instrument (Optovist). As expected, CS was shown to decrease in the presence of glare, in dynamic driving conditions, and as a function of age (all P < 0.01). Conclusions: CS and low contrast VA predict night driving ability (operationalized as median hazard detection distance) in a manner that conventional high contrast VA does not. Either may therefore provide a useful metric for assessing fitness to drive at night, particularly in older individuals. CS measurements can be made within a driving simulator, and the data are in good agreement with conventional clinical methods (Optovist I).